Individual and joint effects of overweight/obesity and the triglyceride−glucose index on mortality risk in type 2 diabetic patients: a retrospective cohort study in China - Diwon, Anthony; Chen, Yuxin; Chen, Yang; Zhang, Xinlv; Wang, Hui; Wang, Ziyi; Zhang, Guomiao; Sheng, Qichao; Mei, Huiqin; Xu, Yixi; Mao, Qingyang; Zheng, Chao; et al. (Frontiers in Endocrinology, 2026)
BackgroundThe global prevalence of type 2 diabetes mellitus (T2DM) has risen significantly since 1990, contributing substantially to mortality and posing a major public health challenge. While overweight/obesity and insulin resistance, commonly reflected by the triglyceride-glucose (TyG) index, are established risk factors for the development of T2DM, their individual and combined effects on mortality among patients with T2DM remain incompletely elucidated. This study aimed to evaluate the associations between body mass index (BMI) and the TyG index with all-cause and cardiovascular disease (CVD) mortality in a large clinical cohort of type 2 diabetes mellitus (T2DM) patients.MethodsThis retrospective cohort study included 15,796 T2DM adults (aged >18 years) from two hospitals in China (2010-2023). The primary outcome was all-cause mortality, with a mean follow-up duration of 2.8 years. BMI was categorized as normal weight (18.5-24.9 kg/m2), overweight (25-29.9 kg/m2), and obesity (≥30 kg/m2). The TyG index was calculated as ln [fasting triglycerides (mg/dL) × fasting glucose (mg/dL)/2]. Multiple Cox proportional hazards models were used to estimate adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs) for mortality.ResultsAmong 15,796 participants, 1,665 deaths were recorded, including 629 CVD-related deaths. Overweight and obesity were associated with lower all-cause mortality risk (aHR: 0.73, 95% CI: 0.65−0.81 and aHR: 0.86, 95% CI: 0.74−1.00, respectively). Higher TyG index quartiles (Q3 and Q4) were associated with decreased mortality risk (aHR: 0.85, 95% CI: 0.74−0.98; aHR: 0.84, 95% CI: 0.72−0.97). The protective effect of a higher BMI was more pronounced in patients aged 60 years or older.ConclusionOur findings revealed that BMI and the TyG index are associated with mortality risk in T2DM patients, particularly in older patients. However, these findings are observational and do not imply causality or validate prognostic use. Further studies using causal inference methods are necessary to inform clinical guidelines.